Pertanggung Jawaban Hukum Pelaku Tindak Pidana Penyuapan - Valentino Wenno (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: Bribery is a form of corruption. The crime of bribery itself has basically been regulated in Law Number 11 of 1980 concerning the Crime of Bribery. One of the crimes of bribery that occurred to the head of the Angin Timur, namely AL.Purposes of the Research: This writing aims to find out and discuss the forms of legal responsibility for the perpetrators of the crime of bribery.Methods of the Research: The research method in this paper uses a normative juridical research type. The research approach used is a statutory approach and a conceptual approach and a case approach. The procedure for collecting legal materials uses library research, as well as processing and analyzing legal materials in this study using editing, systematization and description processing as well as qualitative analysis.Results of the Research: The form of legal responsibility in the crime of bribery is based on a criminal basis, meaning that in this case criminal liability is appropriate. Then criminal responsibility is basically carried out individually because the actions taken are like individual actions. With reference to criminal liability which is essentially carried out individually, there is a very important relationship from this form of criminal responsibility, (1) namely the indication of a criminal act; (2) Perpetrators because of their actions are capable of being held accountable; (3) There is intentional or negligence; and (4) There is no forgiveness for the actions of the perpetrator.